Eustress in Space: Opportunities for Plant Stressors Beyond the Earth Ecosystem - Hessel, Volker; Liang, Shu; Tran, Nam Nghiep; Escribà-Gelonch, Marc; Zeckovic, Olivia; Knowling, Matthew; Rebrov, Evgeny; This, Herve; Westra, Seth; Fisk, Ian; Gilliham, Matthew; Burgess, Alexandra (Frontiers in Astronomy and Space Sciences, 2022)
Human space exploration cannot occur without reliable provision of nutritious and palatable food to sustain physical and mental well-being. This ultimately will depend upon efficient production of food in space, with on-site manufacturing on space stations or the future human colonies on celestial bodies. Extraterrestrial environments are by their nature foreign, and exposure to various kinds of plant stressors likely cannot be avoided. But this also offers opportunities to rethink food production as a whole. We are used to the boundaries of the Earth ecosystem such as its standard temperature range, oxygen and carbon dioxide concentrations, plus diel cycles of light, and we are unfamiliar with liberating ourselves from those boundaries. However, space research, performed both in true outer space and with mimicked space conditions on Earth, can help explore plant growth from its ‘first principles’. In this sense, this perspective paper aims to highlight fundamental opportunities for plant growth in space, with a new perspective on the subject. Conditions in space are evidently demanding for plant growth, and this produces ‘stress’. Yet, this stress can be seen as positive or negative. With the positive view, we discuss whether plant production systems could proactively leverage stresses instead of always combatting against them. With an engineering view, we focus, in particular, on the opportunities associated with radiation exposure (visible light, UV, gamma, cosmic). Rather than adapting Earth conditions into space, we advocate on rethinking the whole issue; we propose there are opportunities to exploit space conditions, commonly seen as threats, to benefit space farming.